The Diagnostic Behavioral Assessment for autism spectrum disorder - Revised: A screening instrument for adults with intellectual disability suspected of autism spectrum disorders - Sappok, T.; Gaul, I.; Bergmann, T.; Dziobek, I.; Bolte, Sven; Diefenbacher, A.; Heinrich, M. (Elsevier Inc., 2014)
Given the strong association between intellectual disability (ID) and autism spectrum disorder (ASD), standardized instruments for the assessment of ASD in adults with ID are desirable. The Diagnostic Behavioral Assessment for ASD - Revised (DiBAS-R) is a DSM-5/ICD-10 based caregiver-report screening tool that consists of 19 Likert-scaled items. This study evaluated the item-validities, item-difficulties, item-variances, part-whole corrected item total-correlations, reliability, and the factorial, diagnostic, and convergent/discriminant validities of the DiBAS-R in a clinical, adult ID sample (N = 219). Factor analysis yielded two consistent dimensions; i.e., social interaction/communication and stereotypy/rigidity/sensory abnormalities. The diagnostic validity was adequate, as reflected by an area under the curve of 0.89 and balanced sensitivity and specificity values of 81%. The DiBAS-R total scores were significantly correlated with the Social Communication Questionnaire (r = 0.52), the Scale for Pervasive Developmental Disorders in Mentally Retarded Persons (r = 0.50), and the Autism-Checklist (r = 0.59), while no significant correlation with the Modified Overt Aggression Scale was observed. The interrater reliability was excellent (ICC = 0.88). These findings indicate that the DiBAS-R is a promising and psychometrically sound instrument for ASD screening of adults with ID. © 2014 Elsevier Ltd.